ChemInform Abstract: Catalytic Enantioselective Intramolecular Cyclization of N‐Aryl Diazoamides Using a Titanium—BINOLate Complex. Issue 33 (19th August 2014) - Hashimoto, Takuya; Yamamoto, Kumiko; Maruoka, Keiji
Abstract Addition of an external proton source such as 4‐bromo‐2, 6‐di‐tert‐butylphenol allows a lowered catalyst loading, while slightly decreasing the yield and enantiomeric excess as well as prolonging the reaction time.